HUBUNGAN PENGETAHUAN DAN SIKAP IBU DENGAN KETEPATAN PEMBERIAN MP-ASI PADA BAYI DIKELURAHAN TIGABALATA KECAMATAN JORLANG HATARAN KABUPATEN SIMALUNGUN TAHUN 2015 - Devi Simbolon; Heru Santosa; Asfriyati . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Breastfeeding supplementary food is a supplementary food other than breast milk given to the baby after the baby is 6 months old. In addition to breastfeeding supplementary food, breast milk should still be given to the baby, at least until 24 months. The cause of the baby's growth disorders is due to the provision of complementary feeding by mothers who do not conform with the precision timing, frequency, type, number of foodstuffs, and the weave. The objective of the research was to investigate the relation between knowledge and mother attitude with the breastfeeding supplementary food in giving to the babies at the Tigabalata village in 2015.   This type of research is a survey of analytical by using cross sectional design,the population in the study were all women who had a baby 24 months as many as 57 infants and serve as the total sample. Data was obtained through interviews using a questionnaire and analyzed by chi-square test.   From the results of the chi-square test (α <0.05), indicating there is a significant relationship between the knowledge with accuracy gift weaning infants obtained p = 0.002. And there is a significant relationship between the attitude of a mother with the breastfeeding supplementary food to the babies obtained p = 0.029.   Expected to health workers who work at the health center Tiga Balata more routine counseling on appropriate complementary feeding to mothers personally. Also to mothers who have babies to more frequent follow Posyandu activities and counseling are held in villages as well as increased knowledge and search for health information, especially the provision of complementary feeding.   Keywords: Knowledge, Attitude, Breastfeeding Suplementary food